MOBILE APPLICATIONS AND THEIR IMPORTANCE IN THE COMMERCIAL WORLD - Luján Miranda Lezcano, Ilsen; Daniel Lopez Romero, Jonathan; Emanuel Cañete Gonzalez, Lucas; Gabriel Zacarías, Fernando; Graciela Ortega Dominguez, Myrian; Zarate Centurión, Cristhian (Revista Gênero e Interdisciplinaridade, 2023)
The Mobile applications and their importance within the commercial world, focus many people today since it is a communication barrier in the educational and work environment, because it is based on its ability to improve various aspects of our daily life, since they provide great comfort and accessibility for users, facilitating access to services such as commerce on social networks, online education, among many more. The methodology used is the research is of the quantitative approach, the data collection was carried out through a survey with semi-open questions, the results of the survey indicate that 83% of people frequently use mobile applications, in context the advantages and opportunities offered by the development of new commercial business methods through mobile applications. As a result of the research it shows that the use of mobile applications is deeply rooted in the commercial industry and allows the business to take advantage of the wide range of capabilities to achieve objectives. In conclusion, mobile applications are fundamental in the commercial world, as they allow reach a broader audience, offer personalized services, improve efficiency and productivity, and transform entire industries.